Employee Satisfaction and Its Determinants Among Healthcare Staff in District Hospitals of Kashmir: A Cross-Sectional Study - Asmat Parveen; Haroon Rashid; Noorul Amin; Ulfat Amin; Mubashir Bashir; Rohi Jan; Andleeb Yousuf; Roohi Jan; Humaira Qadir; Amir Suhail; Foziya Manzoor; Kahkashan Nabi (Fundamental and Management Nursing Journal, 2026)
Introduction: Employee satisfaction is a key determinant of organizational performance, particularly in healthcare settings where motivated staff are essential for delivering high-quality patient care. Limited regional evidence exists regarding workforce engagement and retention in Kashmir. This study aimed to assess employee satisfaction and its associated demographic and job-related factors among healthcare workers in district hospitals of Kashmir. Method: A descriptive cross-sectional study was conducted among 236 healthcare employees from three district hospitals using consecutive sampling. Data were collected through a validated structured interview schedule covering domains such as job satisfaction, autonomy, recognition, co-worker relationships, pay, supervision, and promotion opportunities. Statistical analysis included descriptive statistics and inferential tests (chi-square, ANOVA, and Kruskal–Wallis), with significance set at p < 0.05. Results: The overall mean job satisfaction score indicated a moderate level of satisfaction (151.57 ± 30.99), reflecting diverse perceptions among employees. Higher satisfaction was observed in teamwork, co-worker relationships, and supervision, while dissatisfaction was reported regarding pay, rewards, promotion opportunities, and job facilities. Satisfaction was significantly associated with designation, professional education, and marital status, whereas age, gender, residence, and general education showed no significant relationship. Conclusion: Healthcare employees in Kashmir’s district hospitals demonstrate moderate but uneven satisfaction. Strengthening compensation policies, ensuring transparent promotion systems, and expanding professional development opportunities are critical to enhancing employee morale, retention, and institutional performance.